Pengaruh Penataan Produk dan Brand Image Terhadap Impulse Buying di Superindo Menur Surabaya - Hestin Rinda; Liling Listyawati; Hadi Sugiyanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to find out and analyze the influence of product structuring and Brand Image on Impulse Buying in Superindo Menur Surabaya. The variables used in this study are independent variables (X) and dependent variables (Y). The independent variables in this study are product structuring (X1) and Brand Image (X2), while the dependent variable (Y) is Impulse Buying In this study, a quantitative approach is used by collecting data through questionnaires, library studies, and documentation. The population used is all consumers who have made a purchase at Superindo Menur Surabaya at least once. Using a sampling technique, namely a non-probability technique with a purposive sampling method with the following criteria: consumers, both men and women aged 18-50 years who are in the city of Surabaya, have visited at least one time at Superindo Menur Surabaya. The data in this study were tested using validity tests, reliability tests, classical assumption tests, multiple linear regressions, and hypotheses. The results of this study show that product structuring has a significant effect on impulse buying, brand image has a significant effect on impulse buying, product structuring and brand image have a significant effect together on impulse buying in Superindo Menur Surabaya.